How a grateful leader trait can cultivate creative employees: A dual-level leadership process model. Issue 3 (4th May 2022) - Li, Chenwei; Wu, Chia-Huei; Brown, Michael E.; Dong, Yuntao
ABSTRACT: Does trait gratitude shape leaders' behavior and thus followers' outcomes? We developed and tested a model linking leader's trait gratitude to ethical leadership and leader–member exchange (LMX), and examine their impacts on followers' felt psychological safety and thus creativity at work. Using multi-wave, multi-source survey data from 295 subordinates and 76 supervisors, we found that leader's trait gratitude was positively associated with ethical leadership at the team level and LMX at the individual (follower) level. In turn, both ethical leadership and LMX contribute to followers' felt psychological safety and ultimately improve creative performance at work. Our study extends gratitude research by examining how trait gratitude can shape leadership influence on followers.